Start-ups in camouflage: the convergence of MSMEs, innovation, and Indian defense needs - Rohit Mohite; Ravi Chaurasiya; Sandeep Sharma; Sandesh Akre (Defense and Security Studies)
The integration of Micro, Small, and Medium Enterprises (MSMEs), particularly start-ups, into India's defense sector is emerging as a transformative force in modernizing the country's military capabilities. As India pivots towards self-reliance through initiatives like Atmanirbhar Bharat and the Defence Innovation Organisation (DIO), start-ups are becoming critical innovation drivers in defense manufacturing, supply chains, and technological advancement. This paper investigates the current and potential convergence of start-ups and MSMEs with Indian defense needs, analyzing policy frameworks, innovation hubs, funding ecosystems, and dual-use technologies. A mixed-methods approach comprising policy analysis, case studies (e.g., Tonbo Imaging, IdeaForge), and primary interviews with defense ecosystem stakeholders is employed. The findings suggest a positive correlation between MSME innovation intensity and their integration into strategic defense functions. However, structural bottlenecks such as procurement delays, intellectual property risks, and lack of sustained funding restrict their scaling. The study proposes a techno-policy roadmap to deepen civil-military-industrial integration through innovation clusters, regulatory sandboxing, and joint development programs. The outcomes offer a blueprint for leveraging entrepreneurial vigor to meet national security imperatives while fostering indigenous defense technology capabilities.